2008
DOI: 10.1186/1472-6963-8-207
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of health care utilization by immigrants in Portugal

Abstract: Background: The increasing diversity of population in European Countries poses new challenges to national health systems. There is a lack of data on accessibility and use of health care services by migrants, appropriateness of the care provided, client satisfaction and problems experienced when confronting the health care system. This limits knowledge about the multiple determinants of the utilization of health services. The aim of this study was to describe the access of migrants to health care and its determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
90
1
20

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(125 citation statements)
references
References 38 publications
11
90
1
20
Order By: Relevance
“…Some authors refer that women's perspectives on the delivered health care and the degree of satisfaction with the health system are strongly influenced by their expectations of care and previous experiences in the country of origin (Gurman and Becker 2008;Sofaer and Firminger 2005). Therefore, it is possible to admit that among participants, those from countries that lack health care structures may perceive health care services in Portugal as of higher quality while others from countries with a more efficient health system may perceive those services as less competent, like previous studies suggest (Dias et al 2008;Gurman and Becker 2008).…”
Section: Discussionmentioning
confidence: 79%
See 3 more Smart Citations
“…Some authors refer that women's perspectives on the delivered health care and the degree of satisfaction with the health system are strongly influenced by their expectations of care and previous experiences in the country of origin (Gurman and Becker 2008;Sofaer and Firminger 2005). Therefore, it is possible to admit that among participants, those from countries that lack health care structures may perceive health care services in Portugal as of higher quality while others from countries with a more efficient health system may perceive those services as less competent, like previous studies suggest (Dias et al 2008;Gurman and Becker 2008).…”
Section: Discussionmentioning
confidence: 79%
“…It is important to assess women's perceptions and perceived needs concerning health care to better understand the challenges they face in accessing and using health care services. Research on access and utilization of health care services of immigrants has based mainly on quantitative data (Dias et al 2008;Marshall et al 2005;Stronks et al 2001); lack of information on women's perspectives on these issues remains.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The results showed that people born outside Spain use EHS differently and more frequently than native born people in Spain. In Portugal an investigation of hospital utilization [5] collected data for 1,513 migrants. This work showed that age, length of stay, legal status and economic situation were interrelated in health services usage.…”
Section: Health Services Utilization Studies For Large Data Setsmentioning
confidence: 99%